2014
DOI: 10.1016/j.jfca.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on flavanones, the major citrus polyphenols

Abstract: The consumption of Citrus fruits and juices has been widely investigated for its possible role in the prevention of cardiovascular disease and cancer. These beneficial effects are mainly attributed to flavanones, the typical polyphenols of Citrus species. Major flavanones in plant species include hesperetin, naringenin, eriodictyol, isosakuranetin and their respective glycosides. Hesperetin and its derivatives are characteristic flavanones of sweet orange, tangelo, lemon and lime, while naringenin and its deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
265
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(276 citation statements)
references
References 214 publications
(212 reference statements)
8
265
0
3
Order By: Relevance
“…The identification of specific flavanones has grown dramatically over the past 20 y, from a handful of compounds to >400 naturally occurring isolates (102). Interestingly, flavanones are precursor molecules to the other flavonoids (102).…”
Section: Flavanonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of specific flavanones has grown dramatically over the past 20 y, from a handful of compounds to >400 naturally occurring isolates (102). Interestingly, flavanones are precursor molecules to the other flavonoids (102).…”
Section: Flavanonesmentioning
confidence: 99%
“…The major flavanones, naringenin and hesperetin, are commonly found in tomatoes and citrus fruits, and are at their highest concentrations in the peels (102).…”
Section: Flavanonesmentioning
confidence: 99%
“…Flavanones are distributed throughout the plant kingdom and are found in 42 plant families, both in aerial and belowground tissue. These compounds have been shown to possess radical scavenging, anti-inflammatory, and chemopreventive effects [21]. Flavanones in ashitaba, though less studied than the chalcones 1 and 2, have been studied most for their potential as chemopreventive agents [17].…”
Section: Flavanonesmentioning
confidence: 99%
“…Flavonoids 1-10 were previously isolated from sweet oranges (C. sinensis). [18][19][20][21][22][23][24][25] The total concentration of flavonoids in the sample analyzed was 160.0 mg mL -1 and it was injected 20 times , respectively. This study showed the high quality and potential of the Brazilian CFPW considering the investigated compounds, which could serve as an inexpensive and readily available source of polymethoxylated flavonoids.…”
Section: Resultsmentioning
confidence: 99%